STUDI TENTANG PENGGUNAAN BAHAN AJAR EKONOMI MATERI AKUNTANSI KELAS XI IPS SMA NEGERI 3 - APRILIA FANIATI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
The feasible teaching materials on the based of Badan Standar Nasional Pendidikan (BSNP) which is used in learning process willhelp teacher and student in the learning process. This study aims to determine what teaching materials are used and the reasons teacher using it, the feasibility of the teaching materials used assessed the feasibility of the component based on the content, presentation, language, andgraph, and the student’s responses to teaching materials used in teaching accounting SMA Negeri 3 Sidoarjo. The data collection methode uses documentation, interview, and questionare. The results of this study indicate that teacher use teaching materials are text books and worksheets. Teacher used it because the content of the book has been matching with SK/KD on the syllabus to get the goal of learning process. Phibeta textbook is very feasible for being used as teaching material in learning process, while Viva Pakarindo worksheet is feasible for being used as teaching material in learning process. student’sresponses to teaching materials worksheets is agree with the use of the teaching materials. Keywords : teaching materials, feasibility, student’s responses